Efficient data delivery in dense reader environment of passive sensor network - Nawaz, F. (Springer, 2020)
Wireless Sensor Network (WSN) is a self-organizing network which is mostly employed in industrial scale. In this network, there is random dispersion of nodes in order to sense diverse range of parameters. The main objective of this research paper is to scrutinize the design of Wireless Surface Acoustic Wave (SAW) Sensor Network (WSSN). Passive SAW sensor is a ridged sensor which is best suited to monitor harsh environmental condition. It works in a dense reader environment for stable communication because it has a narrow connectivity radius. In this research paper, the viability analysis has been performed, utilizing WirelessHART (WH) connectivity protocol, by gauging the operation of WSSN with simulator and emulator in aggregation, in order to support the practicality of WSSN. The results have shown that WH can be relied upon and implemented in a Dense Reader Environment (DRE) for commercial applications. The analysis has also showed the efficiency of WH in rugged and harsh environments. However, WH is not built to operate particularly in DRE. Through our study, a distinctive anti-collision algorithm, NFRA-C is proposed, which is in line with protocols of the WSSN and WH. NFRA-C provides noise free connectivity in WSSN as compared to other protocols. A power proficient standard (GREEN protocol) with capabilities of network coding is analyzed for WSSN. GREEN protocol even works in DRE producing high packet transmission percentage because the protocol arrangement is used with the network coding and retransmission request capabilities. Â© 2019, Springer-Verlag GmbH Germany, part of Springer Nature.